Real Convergence in Central and Eastern Europe: An Empirical Analysis - Gockov, GJorgji; Makreshanska mladenovska, Suzana; Petrevski, Goran; Trpeski, LJube (Ss Cyril and Methodius University in Skopje, Faculty of Economics - Skopje, 2019)
The process of integration of the former transition economies in the European Union (EU) is associated with numerous problems and challenges. The readiness and suitability of the country for integration within the EU is directly dependent on the achieved nominal and real convergence. Without this convergence, the integration process would face in the future risks of asymmetric shocks, which would generate poor economic performance in the absence of alternative adjustment mechanisms. This paper deals with the process of convergence of the Central and Eastern European (CEE) countries towards the EU and attempts to identify the main driving factors behind this process. In these regards, we first provide an overview of the real convergence through an analysis of several economic variables – rate of approximation of real GDP per capita and price levels, trade integration, harmonization of the economic structure and achievements in the labor market. In addition, we offer a formal econometric evidence on the main determinants of the convergence process, based on a panel data for 10 CEE countries during 2000-2015 period, estimated with fixed effects. The results of our study imply that higher savings and investment ratio, higher labour productivity, more efficient labour markets (lower unemployment) and macroeconomic stability (lower inflation and lower budget deficits) are conducive to real convergence.
Keywords: Real convergence, European Union, Central and Eastern Europe, Panel data models, Fixed-effects estimator